Spinal Cord Blood Flow and Ischemic Injury after Experimental Sacrifice of Thoracic and Abdominal Segmental Arteries - Etz, Christian D. (2008)
OBJECTIVE: Spinal cord blood flow (SCBF) after sacrifice of thoracoabdominal aortic segmental arteries (TAASA) during thoracoabdominal aortic aneurysm (TAAA) repair remains poorly understood. This study explored SCBF for 72h after sacrifice of all TAASA. METHODS: Fourteen juvenile Yorkshire pigs underwent complete serial TAASA sacrifice (T4-L5). Six control pigs underwent anesthesia and cooling to 32C with no TAASA sacrifice. In the experimental animals, spinal cord function was continuously monitored using motor evoked potentials (MEP) until 1 hour (h) after clamping the last TAASA. Fluorescent microspheres enabled segmental measurement of SCBF along the entire spinal cord before, and 5 min, 1h, 5h, 24h and 72h after complete TAASA sacrifice. A modified Tarlov score was obtained for 3 days after surgery. RESULTS: All the pigs with complete TAASA sacrifice retained normal cord function (MEP) until 1h after TAASA ligation. 7 pigs (50%) with complete TAASA sacrifice recovered after 72h; 7 pigs suffered paraparesis or paraplegia. Intraoperatively— and until 1h postoperatively— SCBF was similar among the three groups along the entire cord. Postoperatively, SCBF did not decrease in any group, but significant hyperemia occurred at 5 hours in controls and recovery animals, but did not occur in pigs that developed paraparesis or paraplegia in the T8-L2 segments (p=.0002) and L3-S segments (p=.0007). At 24h, SCBF remained marginally lower from T8 caudally; at 72h, SCBF was similar among all groups along the entire cord. SCBF in the segments T8-L2 at 5h predicted functional recovery (p=.003). CONCLUSIONS: This study suggests that critical spinal cord ischemia after complete TAASA sacrifice does not occur immediately (intraoperatively), but is delayed 1–5 hours or longer after clamping, and represents failure to mount a hyperemic response to rewarming and awakening. The short duration of low SCBF associated with spinal cord injury suggests that hemodynamic and metabolic manipulation lasting only 24–72 hours may allow routine preservation of normal cord function despite sacrifice of all TAASA secondary to surgical or endovascular repair of large TAAA.